2015
DOI: 10.1002/jsfa.7134
|View full text |Cite
|
Sign up to set email alerts
|

Phytoecdysteroids and flavonoid glycosides among Chilean and commercial sources of Chenopodium quinoa: variation and correlation to physico‐chemical characteristics

Abstract: BACKGROUND Little is known about varietal differences in the content of bioactive phytoecdysteroids (PE) and flavonoid glycosides (FG) from quinoa (Chenopodium quinoa Willd.). The aim of this study was to determine the variation in PE and FG content among seventeen distinct quinoa sources and identify correlations to genotypic (highland vs. lowland) and physicochemical characteristics (seed color, 100-seed weight, protein content, oil content). RESULTS PE and FG concentrations exhibited over 4-fold differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 54 publications
(169 reference statements)
2
27
1
Order By: Relevance
“…Our results suggest that these factors affected protein and fat accumulations and seed size in a way which is not related to the distribution of nutrients among different tissues within the seed and point out the specific environmental and genetic effects on each of these components. The positive association found between embryo/seed size and lipid content is consistent with results found previously in quinoa (Graf et al., ; Miranda et al., ), the negative association with protein content contrast with results found in those studies. On the other hand, the correlations found in this study are consistent with results found in sunflower for seed oil concentration (where changes were also explained by those in seed weight and not by the embryo relative proportion) (Aguirrezábal et al., ).…”
Section: Resultssupporting
confidence: 92%
“…Our results suggest that these factors affected protein and fat accumulations and seed size in a way which is not related to the distribution of nutrients among different tissues within the seed and point out the specific environmental and genetic effects on each of these components. The positive association found between embryo/seed size and lipid content is consistent with results found previously in quinoa (Graf et al., ; Miranda et al., ), the negative association with protein content contrast with results found in those studies. On the other hand, the correlations found in this study are consistent with results found in sunflower for seed oil concentration (where changes were also explained by those in seed weight and not by the embryo relative proportion) (Aguirrezábal et al., ).…”
Section: Resultssupporting
confidence: 92%
“…Among edible agricultural crops, quinoa seeds contain the highest levels of phytoecdysteroids (Table ), polyhydroxlyated steroids that are structurally related to insect molting hormones involved in plant defense (Dinan ) and documented to exert a myriad of biological activities in mammals relevant to human health. Quinoa has been shown to contain a range of 138 to 570 μg/g total phytoecdysteroids (Graf and others ). At least 13 different phytoecdysteroids have been isolated from quinoa seeds, of which 20‐hydroxyecdysone (20HE) (Figure C) was the most abundant (62% to 90% of total phytoecdysteroids).…”
Section: Phytochemistry and Nutritional Value Of Quinoamentioning
confidence: 99%
“…At least 13 different phytoecdysteroids have been isolated from quinoa seeds, of which 20‐hydroxyecdysone (20HE) (Figure C) was the most abundant (62% to 90% of total phytoecdysteroids). The second most abundant set of phytoecdysteroids in quinoa include makisterone A, 24‐epi‐makisterone A, and 24(28)‐dehydromakisterone A (Zhu and others ; Kumpun and others ; Graf and others , ).…”
Section: Phytochemistry and Nutritional Value Of Quinoamentioning
confidence: 99%
See 1 more Smart Citation
“…Chenopodium quinoa Willd. (quinoa) is one of the oldest cultivated plants in the Andean region and is well known as a functional food and nutraceutical source rich in essential amino acids, unsaturated fats, phytoecdysteroids, flavonoids, phenolic acids, betalains, and saponins, which can allegedly reduce the risk of cardiovascular disease, cancer, osteoporosis, and diabetes [20][21][22][23][24][25][26][27][28][29][30][31]. For example, flavonoids are commonly used to treat and prevent diabetes and obesity [32,33], while 20-hydroxyecdysone is believed to exhibit antioxidant, antidiabetic, anti-obesity, antihypertensive, anticancer, and anti-inflammatory properties [34,35].…”
Section: Introductionmentioning
confidence: 99%